AUDIATUR ET ALTERA PARS - Kristan, Silvo (Šport (Ljubljana), 2024)
Although I promised the editor that I would not comment again, the temptation is too great. I find it difficult to accept sophistical and ideological acrobatics and other such tricks, which is why I resist all kinds of manipulations that are spread by anyone. It is only right that the readers should also read the dissenting opinion (altera pars), because only this can stimulate reflection and testing of the author's credibility. Unfortunately, for the sake of clarity and comprehensibility, I must repeat myself here and there. Not least because my interlocutor keeps repeating himself in our correspondence without any further argument. This contribution can also be seen as a supplement to the contribution by Ž. Kozinc and J. Žitnik, who in the previous issue of Sport (1–2, 2024, pp. 5–12) pointed out some of the slip-ups in the research of the field of sport. Both authors point out the weaknesses of research work, such as inaccurate presentation of facts, falsification of data, bias of authors, selective reporting, reporting of half-truths, unjustified generalisations, manipulation of readers, etc. I write about these in detail in my contribution. The only difference is that these authors focus in principle (without concrete examples) on the empirical cognitive branch, while I limit myself to the theoretical cognitive branch (monographs, debates, polemics, etc.) and point out the shortcomings with concrete examples and argued facts (with evidence).
Keywords: šport; znanost